Neonatal myoclonus in Bryant-Li-Bhoj syndrome associated with a novel H3F3A variant - Moemi Hojo; Noriko Soma; Kei Yamada; Yu Kobayashi; Masaki Miura; Hitomi Fujii; Hiromi Nyuzuki; Yosuke Nishio; Taichi Oso; Tomoo Ogi; Takeshi Ikeuchi; Jun Tohyama (Human Genome Variation)
Abstract Bryant-Li-Bhoj syndrome (BLBS; OMIM # 619720, 619721), caused by germline H3F3A and H3F3B variants encoding histone H3.3, is characterized by mild to severe developmental delay, intellectual disability, failure to thrive, muscle tone abnormalities, and dysmorphic facial features. Here, we present a Japanese patient with a novel heterozygous p.A48G variant in H3F3A, displaying previously unrecognized symptoms of neonatal myoclonus. This case helps broaden the phenotypic spectrum of BLBS.